Projektna naloga za tehniko in tehnologijo - Papotnik, Amand (Les (Ljubljana), 2000)
The paper deals with the project task as strategy of education-training activities. The project task is organised starting from conception through prototype, technical and technological documentation, execution of series production to analysis of work and evaluation of product - project. In such a task the pupils of several clasess or different classes can cooperate so that the work is divided among classes. The project task is a strategy of education-training activities including the developing of divergent thinking, creative capacities, acquiring, developing, exercising and applying of knowledge in the area of technology, organization of work, economics, ergonomics, ecology, information processing and computer science, industrial design etc.
Keywords: tehnični pouk; projektne naloge; metodika